Immune response to SARS‐CoV‐2 and mechanisms of immunopathological changes in COVID‐19. Issue 7 (11th July 2020) - Azkur, Ahmet Kursat; Akdis, Mübeccel; Azkur, Dilek; Sokolowska, Milena; van de Veen, Willem; Brüggen, Marie‐Charlotte; O'Mahony, Liam; Gao, Yadong; Nadeau, Kari; Akdis, Cezmi A.
Abstract: As a zoonotic disease that has already spread globally to several million human beings and possibly to domestic and wild animals, eradication of coronavirus disease 2019 (COVID‐19) appears practically impossible. There is a pressing need to improve our understanding of the immunology of this disease to contain the pandemic by developing vaccines and medicines for the prevention and treatment of patients. In this review, we aim to improve our understanding on the immune response and immunopathological changes in patients linked to deteriorating clinical conditions such as cytokine storm, acute respiratory distress syndrome, autopsy findings and changes in acute‐phase reactants, and serum biochemistry in COVID‐19. Similar to many other viral infections, asymptomatic disease is present in a significant but currently unknown fraction of the affected individuals. In the majority of the patients, a 1‐week, self‐limiting viral respiratory disease typically occurs, which ends with the development of neutralizing antiviral T cell and antibody immunity. The IgM‐, IgA‐, and IgG‐type virus‐specific antibodies levels are important measurements to predict population immunity against this disease and whether cross‐reactivity with other coronaviruses is taking place. High viral load during the first infection and repeated exposure to virus especially in healthcare workers can be an important factor for severity of disease. It should be noted that many aspects of severe patients are unique to COVID‐19 and are rarely observed in other respiratory viral infections, such as severe lymphopenia and eosinopenia, extensive pneumonia and lung tissue damage, a cytokine storm leading to acute respiratory distress syndrome, and multiorgan failure. Lymphopenia causes a defect in antiviral and immune regulatory immunity. At the same time, a cytokine storm starts with extensive activation of cytokine‐secreting cells with innate and adaptive immune mechanisms both of which contribute to a poor prognosis. Elevated levels of acute‐phase reactants and lymphopenia are early predictors of high disease severity. Prevention of development to severe disease, cytokine storm, acute respiratory distress syndrome, and novel approaches to prevent their development will be main routes for future research areas. As we learn to live amidst the virus, understanding the immunology of the disease can assist in containing the pandemic and in developing vaccines and medicines to prevent and treat individual patients.